BIOLOGICALLY ACTIVE COMPOUNDS OF ARTEMISIA ANNUA. SESQUITERPENE LACTONES - D. A. Konovalov; O. M. Shevchuk; L. A. Logvinenko; A. A. Khamilo (Фармация и фармакология (Пятигорск))
Artemisia annua is an herblike annual plant which has been used in Chinese folk medicine for more than 2,000 years. In 1970-s sesquiterpene lactones of artemisinin was isolated from the aboveground part of this plant. Today it is the most efficient known natural and synthetic compound for malaria treatment.The purpose of the study was the review of the information from the open sources about the study for sesquiterpene lactones of Artemisia annua referring to its pharmacological activity.Methods. The study was carried out using informational and search engines (PubMed, ScholarGoogle), library databases (eLibrary, Cyberleninca), and the results of our own researches.Results. It was established that apart from the essential oil and phenolic compounds, aboveground part of Artemisia annua, it contains a significant amount of sesquiterpene lactones. Qualitative content and quantitative composition of sesquiterpene lactones varies depending on the ecological and geographic factors, plants growing phase, cultivation technology, drying methods etc. Well-known pharmacological studies of the extracts from Artemisia annua herb with sesquiterpene lactones, as well as individual compounds of this group characterize this type of raw materials as a perspective source for more profound research.Conclusion. Our analysis of the open materials on the sesquiterpene lactones of Artemisia annua, including phytochemical and pharmacological ones, allows characterization of the Artemisia annua herb as a perspective source for new drugs working out.